Determining The Ratio Of Pressure And Compressor Air Mass Flow Rate To Generate Thrust - Suherman Mukti; Erzi Agson Gani; Maykel Manawan; Ansori (CV. AFDIFAL MAJU BERKAH, 2023)
Missiles are strategic defense equipment that have a high deterrent effect in the national defense system because they have high destructive power, high precision, and can be launched remotely. With the above characteristics, the missile is a high-tech product, and it still needs a lot of engineering effort to master the technology, especially the propulsion / propulsion system technology which is mostly in the form of turbojet engines. With the above background, this study designs and analyzes one of the main components of the missile propulsion system, namely the compressor impeller. This study analyzes the pressure ratio and mass flow rate of compressor air whose values are used to obtain the impeller design of a small turbojet engine compressor on a surface-to-surface cruise missile propulsion system. The method used is analytical method. The conclusion of the study is that the combination of a compressor pressure ratio of 4 and an air mass flow rate of 2.5 kg/s can produce a target thrust of 1,300 N, and the diameter of the turbojet engine is smaller than the maximum allowable space diameter of 270 mm.